OA29 Clinical outcomes up to week 48 of filgotinib treatment in an ongoing long-term extension trial of RA patients with inadequate response to methotrexate initially treated with filgotinib or adalimumab during the Phase 3 Parent Trial. (23rd April 2022) - Combe, Bernard; Tanaka, Yoshiya; Emery, Paul; Pechonkina, Alena; Kuo, Albert; Gong, Qi; Van Beneden, Katrien; Rajendran, Vijay; Schulze-Koops, Hendrik
Abstract: Background/Aims: The preferential Janus kinase (JAK)-1 inhibitor filgotinib (FIL) is approved for treatment of moderately to severely active RA in Europe and Japan. We assessed efficacy and safety of FIL in patients (pts) with inadequate response to MTX (MTX-IR) who completed a Phase 3 trial (NCT02889796) and went on to enroll in a long-term extension (LTE; NCT03025308). Methods: Pts who completed the parent study (PS) on study drug were eligible to enter the LTE. LTE data cutoff was June 1, 2020, and safety data are reported to that date, with median exposure 2.2 years. Efficacy data to W48 are reported for 4 treatment groups (all with background MTX): pts who received FIL 200mg (FIL200) or FIL 100mg (FIL100) in the PS and continued their dose in LTE (FIL200/FIL200, FIL100/FIL100) and ADA pts who were re-randomized, double blind, to FIL200 or FIL100 for LTE (ADA/FIL200, ADA/FIL100). ACR20/50/70 response rates, DAS28[CRP] ≤3.2 and <2.6, and CDAI ≤10 and ≤2.8 are reported. Exposure-adjusted incidence rates (EAIR)/100 pt-years of exposure of treatment-emergent adverse events (TEAEs) and AEs of special interest (AESIs) are summarized. Results: As of June 1, 2020, 522/571 (91%) FIL200/FIL200, 502/570 (88%) FIL100/FIL100, 118/128 (92%) ADA/FIL200, and 115/130 (89%) ADA/FIL100 pts were still on study drug. LTE baseline (BL) disease characteristics were similar between groups: mean duration of RA was approximately 8.7 years; DAS28(CRP) was 2.55 and mean MTX dosage was 15.0 mg/week. Proportions of pts achieving ACR20/50/70, DAS28(CRP) ≤3.2, <2.6, and CDAI ≤10, ≤2.8 were maintained in all 4 LTE groups through W48. Numerically greater proportions of pts met response criteria at W48 in the FIL200 groups vs FIL100, regardless of PS treatment. TEAEs, serious AEs, and AEs Grade ≥3 were largely comparable between groups and lowest in ADA/FIL100 pts. There were 3 deaths in each PS FIL group and 2 in each PS ADA group; EAIRs for deaths were lower for FIL/FIL groups compared with ADA/FIL groups. Opportunistic infections occurred only in FIL/FIL pts (2 in each group). Nonmelanoma skin cancer (NMSC; n = 5) occurred only in FIL/FIL groups, and malignancies excluding NMSC occurred in all groups except ADA/FIL100. Conclusion: During the LTE through W48, response rates were maintained for FIL/FIL and ADA/FIL pts. Though there were differences between LTE groups, safety was largely comparable and consistent with that observed in the PS and in previously reported results of safety data from 7 trials: rates of AESIs were low, and all confidence intervals were overlapping. Limitation: the LTE was not formally randomized for comparison between FIL/FIL and ADA/FIL treatment groups, the groups were of unequal size, and the switch from ADA to FIL for LTE was by design, rather than based on disease activity. Disclosure: B. Combe: Consultancies; AbbVie; Eli Lilly & Co.; Gilead Sciences, Inc.; Janssen; Pfizer; Roche-Chugai; and Sanofi. Member of speakers' bureau; for BMS; Eli Lilly & Co.; Gilead Sciences, Inc.; MSD; Pfizer; Roche- Chugai; and UCB. Grants/research support; Novartis, Pfizer, and Roche-Chugai. Y. Tanaka: Consultancies; Eli Lilly, Daiichi- Sankyo, Taisho, Ayumi, Sanofi, GSK, Abbvie. Member of speakers' bureau; Daiichi- Sankyo, Eli Lilly, Novartis, YL Biologics, Bristol-Myers, Eisai, Chugai, Abbvie, Astellas, Pfizer, Sanofi, Asahi-kasei, GSK, Mitsubishi-Tanabe, Gilead, Janssen. Grants/research support; Abbvie, Mitsubishi-Tanabe, Chugai, Asahi-Kasei, Eisai, Takeda, Daiichi-Sankyo. P. Emery: Consultancies; AbbVie, BMS, Celltrion, Gilead, Lilly, Novartis, Roche, Samsung, and Sandoz. Grants/research support; AbbVie, BMS, Lilly, and Samsung. A. Pechonkina: Shareholder/stock ownership; employee and shareholder in Gilead Sciences, Inc. A. Kuo: Shareholder/stock ownership; employee and shareholder in Gilead Sciences, Inc. Q. Gong: Shareholder/stock ownership; employee and shareholder in Gilead Sciences, Inc. K. Van Beneden: Shareholder/stock ownership; employee of and shareholder in Galapagos, NV. V. Rajendran: Shareholder/stock ownership; employee of and shareholder in Galapagos, NV. H. Schulze-Koops: Consultancies; from AbbVie, Amgen, BMS, Celgene, Celltrion, Chugai, Gilead, Janssen, Eli Lilly and Company, Merck Sharp & Dohme, Novartis- Sandoz, Pfizer, Roche, Sanofi. Grants/research support; AbbVie and Novartis.